Safety, Immunogenicity, and Surrogate Markers of Clinical Efficacy for Modified Vaccinia Ankara as a Smallpox Vaccine in HIV-Infected Subjects - Greenberg, Richard N.; Overton, Edgar Turner; Haas, David W.; Frank, Ian; Goldman, Mitchell; von Krempelhuber, Alfred; Virgin, Garth; Bädeker, Nicole; Vollmar, Jens; Chaplin, Paul (The Journal of infectious diseases, 2013)
Background. Human immunodeficiency virus (HIV)—infected persons are at higher risk for serious complications associated with traditional smallpox vaccines. Alternative smallpox vaccines with an improved safety profile would address this unmet medical need. Methods. The safety and immunogenicity of modified vaccinia Ankara (MVA) was assessed in 91 HIV-infected adult subjects (CD4 + T-cell counts, ≥350 cells/mm 3 ) and 60 uninfected volunteers. The primary objectives were to evaluate the safety of MVA and immunogenicity in HIV-infected and uninfected subjects. As a measure of the potential efficacy of MVA, the ability to boost the memory response in people previously vaccinated against smallpox was evaluated by the inclusion of vaccinia-experienced HIV-infected and HIV-uninfected subjects. Results. MVA was well tolerated and immunogenic in all subjects. Antibody responses were comparable between uninfected and HIV-infected populations, with only 1 significantly lower total antibody titer at 2 weeks after the second vaccination, while no significant differences were observed for neutralizing antibodies. MVA rapidly boosted the antibody responses in vaccinia-experienced subjects, supporting the efficacy of MVA against variola. Conclusions. MVA is a promising candidate as a safer smallpox vaccine, even for immunocompromised individuals, a group for whom current smallpox vaccines have an unacceptable safety profile. Clinical Trials Registration. NCT00189904.